Corrigendum to ‘Epidemiological Profile of Oral Health Conditions in Ecuador: A Retrospective Study from 2016 to 2022’ [International Dental Journal, Volume 76, Issue 1, February 2026, 109313] - W.B. Willy Bustillos Torrez; C.M. Cecilia Belén Molina Jaramillo; C.H. Christian Patricio Hernández Carrera; A.G. Ana Patricia Gutiérrez; D.L. Darwin Vicente Luna-Chonata (Elsevier BV, 2026)
The authors regret that Figure 3 is in black and white. The correct Figure 3 is below.(Figure presented) It was also noted that the first authors were appearing in an incorrect order. This has been corrected to show the right order as part of this corrigendum. The authors would like to apologise for any inconvenience caused.
Keywords: EMTREE medical terms